The Effect of Auditor Quality and Remote Audit on Audit Quality in Indonesia: Moderating Role of Information Technology - Arumega Zaferar; Razana Juhaida Johari; Atika Zarefar; M. Rasuli (Jurnal Dinamika Akuntansi, 2024)
Purpose: This study aims to analyze the effect of audit quality and remote audit on audit quality. In addition, this study will also consider the moderating effect of information technology on the effect of auditor quality and remote audit on audit quality. Method: The population of this study were auditors of the Supreme Audit Agency of the Republic of Indonesia Representative of Riau Province. The sample of this research is all auditors in the agency because it uses a saturated sample technique, with 68 respondents. The hypothesis testing used is partial least square (PLS). Findings: The results of this study found that professional scepticism, auditor competence, and remote auditing have a significant positive effect on audit quality. Furthermore, information technology strengthens the effect of auditor professional scepticism on audit quality. However, there is no evidence information technology can strengthen the effect of competence and remote audit on audit quality. Novelty: This study broadens the literature discussing the effect of auditor and remote auditor qualifications and audit quality by considering the moderating role of information technology. This study will provide a new perspective, especially on remote audits, which are still rarely discussed.